STUDI EVALUASI PROGRAM EMPAT BULAN LULUS IQRA JILID 1-6 DI SD MUHAMMADIYAH AMBARKETAWANG 3 YOGYAKARTA - gesang, Anik oktavia; Rofiah, Nurul Hidayati (Jurnal Fundadikdas (Fundamental Pendidikan Dasar), 2018)
The research aims to find out the evaluation result of the implementation of four months program of Iqra pass, to know the supporting and inhibiting factors, and to know the follow up plan of the implementation of the four month program pass Iqra. The research used is evaluative research with descriptive data analysis method. Research subjects are principal, teacher coordinator of program implementer. The research was conducted at SD Muhammadiyah Ambarketawang 3 Yogyakarta by using interview, observation, and documentation. Validity of data using credibility test that is using triangulation of source and technique.The results showed the four-month program Iqra graduated successfully and performed quite well. Supporting factors in the implementation of the program include student activeness, contributions of principals, teachers, learning facilities are quite good, as well as sufficient program funds. As for the inhibiting factors is the lack of parental participation and differences in ability of each child. Based on these results, the four-month Iqra program can be continued by performing several improvements such as in terms of infrastructure, the use of Iqra teaching guidance, and improvements related to the contribution of parents to the program.